2021
DOI: 10.1002/aic.17474
|View full text |Cite
|
Sign up to set email alerts
|

Computational investigation of metal organic frameworks as potential drug carriers for antihypertensive amlodipine

Abstract: Metal organic frameworks (MOFs) have been recognized as promising materials for biomedical applications such as drug storage and drug delivery. In this study, grand canonical Monte Carlo simulations were carried out to investigate the adsorption of an antihypertensive drug amlodipine in 28 different MOFs. Among them, 19 MOFs, which were identified to outperform those traditional materials, were screened to perform molecular dynamic (MD) simulations in order to select promising candidates for drug carriers of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…took advantage of molecular simulation to investigate the absorption and release of amlodipine in 28 different MOFs. [ 182 ] The results showed that 19 types of these MOFs were superior to the traditional materials in terms of amlodipine uptake capacity. Finally, considering the self‐diffusion coefficient and biocompatibility, they used 5 types of MOFs to explore the mechanism of the amlodipine adsorption process.…”
Section: Mofs‐based Therapeutic Agentsmentioning
confidence: 99%
“…took advantage of molecular simulation to investigate the absorption and release of amlodipine in 28 different MOFs. [ 182 ] The results showed that 19 types of these MOFs were superior to the traditional materials in terms of amlodipine uptake capacity. Finally, considering the self‐diffusion coefficient and biocompatibility, they used 5 types of MOFs to explore the mechanism of the amlodipine adsorption process.…”
Section: Mofs‐based Therapeutic Agentsmentioning
confidence: 99%